Jaringan Tata Kelola Kolaboratif yang Mendukung Ekowisata Berkelanjutan: Studi Kasus Pulau Gili Iyang, Indonesia - Lunariana Lubis; M. Husni Tamrin; Moh. Musleh (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
The development of sustainable ecotourism on Gili Iyang Island, known for its high oxygen levels and unique local culture, requires collaboration among diverse stakeholders through effective governance networks. This study investigates the roles and contributions of key stakeholders—including the Sumenep District Tourism, Culture, Youth, and Sports Office (Dinas Pariwisata, Kebudayaan, Pemuda, dan Olahraga Kabupaten Sumenep or Disparbudpora), the Andang Taruna Tourism Awareness Group (Kelompok Sadar Wisata Andang Taruna or Pokdarwis), village governments, and local communities—in developing ecotourism on Gili Iyang Island, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis. Findings show that governance networks are crucial in enhancing community empowerment, building local capacity, and improving infrastructure to support ecotourism. Nevertheless, challenges remain, including limited resources, conflicts between villages, and minimal private-sector engagement. Strengthening Pokdarwis’ managerial capacity, fostering inter-community synergies, and attracting private sector involvement are identified as essential strategies to ensure sustainable ecotourism. This research contributes to the broader literature on collaborative governance in remote island ecotourism, offering practical insights for policymakers and stakeholders aiming to create resilient, community-driven tourism initiatives that can be adapted to similar island settings.